(untitled) (Communication & Society, 2004)
We are presenting the outcomes of a content analysis study on news frames of the reports on Latin America and the Latin Americans in the Spanish press, which is part of content analysis study in a larger immigration research project focusing on news framing in regard of immigrants found in the reports in the Spanish press. Our findings show that some “discourse strategies” are being used to foster a certain illusory correlation that associates Latin America to negative events with negative results. Countries such as Venezuela and Colombia are especially associated with negative issues, like arm conflicts, nature disasters or crime and accident reports, and with human interest and conflict news frames. This gives us an insight into the consequences that such negative news coverage on Latin America (particularly on those countries keeping high migratory flow with Spain) may arise related to stereotype flourishing and prejudiced attitudes.